Top-Ten Tips for Effective Imaging of Axial Spondyloarthritis - Reijnierse, Monique; Eshed, Iris; Gaalen, Floris van (Seminars in Musculoskeletal Radiology, 2019)
Axial spondyloarthritis (axSpA) is a chronic inflammatory condition that encompasses ankylosing spondylitis as well as nonradiographic axSpA and can lead to chronic pain, structural damage, and disability. The disease is strongly associated with the presence of human leukocyte antigen-B27. Early diagnosis of axSpA is significant due to new treatment regimens leading to reduction of inflammation and potentially delaying disease progression. Imaging of the sacroiliac joints and the spine plays an important role in the early diagnosis of spondyloarthritis. In the current review, the top-ten tips for the effective imaging of axSpA are presented to help both radiologists and rheumatologists in using imaging properly and effectively in their clinical practice.
Keywords: axial spondyloarthritis; MRI; spine; radiographs; inflammation